Pichia-expressed recombinant D6 and DARC negatively affect cell migration and invasion of breast cancer cells - Tan, Wee Yee; Khoo, Boon Yin; Chew, Ai Lan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Atypical chemokine receptor proteins are termed ‘decoy proteins’ as their binding to the respective ligands does not lead to a typical signaling pathway but intercepts the action of chemokines. This method of chemokine activity regulation may also function in tumor suppression. D6 and DARC (Duffy Antigen Receptor for Chemokines) have been reported as decoy chemokine receptors in cancer studies. Purified Pichia-expressed D6 and DARC, produced in-house, were used in cell-based studies to test their biological activities. Cell viability tests showed that recombinant D6 and DARC did not affect cell viability significantly, suggesting that they were not involved in breast cancer cell death. Wound healing assays showed that the presence of recombinant D6 or DARC at 10 μg/mL optimally inhibited the migration of breast cancer cells. ELISA showed an inverse relationship between the recombinant proteins and CCL levels in the treated cells. Migration assay using Boyden chamber demonstrated the function of the recombinant proteins in inhibiting chemotaxis activity of treated cells. Invasion assay showed the ability of the recombinant proteins in inhibiting the invasion property of treated cells. Comparison of single and combinatorial effects of the recombinant proteins showed that the combination of D6 and DARC at a 1:1 ratio (10 μg/mL) is most effective in reducing CCL levels and inhibiting the migration and invasion of treated cells. It was shown that the purified Pichia-expressed recombinant D6 and DARC are the negative regulators of breast cancer cell migration and invasion, and the inhibition effects were greater when they were used in combination.